The Social and Political Life of Armenians in the Holy Land - Kostanian, Ararat (Muslim Politics Review, 2022)
A Palestinian Armenian: The Intertwine between the Social and the Political. Varsen Aghabekian. Dar al-Kalima University Press (2021)The Armenian presence in the Middle East, and in the Holy City in particular, goes back thousands of years. Armenians’ presence in the territory dates back to 420AD when they participated in the construction of St James (Sourp Hagop) Convent. By the sixth century, they had constructed sixty-six religious institutions in Jerusalem. Currently, they still play a big role in the social and religious life in the Holy Land, where the Armenian Quarter stands as the one of the essential religious and ethnic pillars of the old city next to the Muslim, Christian, and Jewish quarters. The Holy Land refers to Palestinian territory and some parts of Israel, an area roughly located between the Mediterranean Sea and the Eastern Bank of the Jordan River. But this book is not solely about the history of the Armenians’ presence in Palestine. As reflected in its title, The Intertwine Between the Social and the Political, this book is about the past and the present of the Armenians of Palestine with implications about their future role in Palestinian nation-building.